Correction: structure, absolute configuration, and conformational study of resorcylic acid derivatives and related congeners from the fungus Penicillium brocae. Issue 62 (8th July 2015) - Zhang, Peng; Meng, Ling-Hong; Mándi, Attila; Li, Xiao-Ming; Kurtán, Tibor; Wang, Bin-Gui
<x xml:space="preserve">Abstract</x> Correction for 'Structure, absolute configuration, and conformational study of resorcylic acid derivatives and related congeners from the fungus Penicillium brocae' by Peng Zhang et al., RSC Adv., 2015, 5, 39870–39877.